2019
DOI: 10.18549/pharmpract.2019.3.1545
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory continuing education for pharmacists in a developing country: assessment of a three-year cycle

Abstract: Background:In Lebanon, mandatory continuing education (CE) for pharmacists was implemented in January 2014.Objective:The objectives of this study are to assess 1) the overall adherence to the mandatory CE program, 2) pharmacists’ preferences related to CE, and 3) barriers to adherence to CE.Methods:By the end of October 2017, an evaluation of pharmacists’ participation in the mandatory CE program was conducted using electronic reports available in the Learning Management System (LMS). Descriptive results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…The survey in the present study revealed that the pharmacists had less exposure to clinical basic knowledge and frontier knowledge of disease treatment in their continuing education and daily work, which they generally considered lack of knowledge. Therefore, medication for common clinical diseases [16], frontier knowledge of pharmacy as well as key points in prescription-checking were typically demanded, followed by regulations, query tools and other aspects, while the demand for basic pharmacy knowledge was lowest. Furthermore, supplementary knowledge of tools, such as pharmacy consultation, communication skills [16], drug incompatibility, clinical test and popular science of pharmacy were needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medication for common clinical diseases [16], frontier knowledge of pharmacy as well as key points in prescription-checking were typically demanded, followed by regulations, query tools and other aspects, while the demand for basic pharmacy knowledge was lowest. Furthermore, supplementary knowledge of tools, such as pharmacy consultation, communication skills [16], drug incompatibility, clinical test and popular science of pharmacy were needed. Prescription-checking is an important part of the pharmacists' services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations